Analisis Bibliometrik:Keterkaitan antara Triple Helix dan Open Innovation - Rohmat Hidayatuloh; Tatang Akhmad Taufik (Politeknik Ganesha Medan, 2023)
This research examines the correlation between Triple Helix and Open Innovation. The study aims to determine: (1) the development of the number of international publications related to Triple Helix and Open Innovation from 2003 to 2023; (2) the mapping of topics related to Triple Helix and Open Innovation based on co-word analysis; (3) the collaboration among authors or researchers related to Triple Helix and Open Innovation. Data collection was done by retrieving publication data from Google Scholar using the